2017
DOI: 10.1186/s12879-017-2437-2
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the sources and antimicrobial resistance patterns of Salmonella isolated from the poultry industry in Southern Ethiopia

Abstract: BackgroundEthiopia set an ambitious masterplan to increase chicken meat and egg production from 2015 to 2020. Poultry breeding, multiplication and distribution centers in the country have received executive order to import, amplify and distribute commercial chickens to end users. The biosecurity and the pathogen fauna of the centers have not been evaluated as to whether the centers could implement the mission effectively without any risk. Thus, the aim of this study was to evaluate the biosecurity practices an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
51
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 42 publications
14
51
7
Order By: Relevance
“…This may be attributed to the very limited use of these antibiotics in the layer farms in the current period. Similarly, Abdi et al (2017) indicated that gentamicin is still effective against Salmonella regardless of the time or location of the study. Ramatla et al (2019) reported that 4% of Salmonella isolates were resistant to gentamicin.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This may be attributed to the very limited use of these antibiotics in the layer farms in the current period. Similarly, Abdi et al (2017) indicated that gentamicin is still effective against Salmonella regardless of the time or location of the study. Ramatla et al (2019) reported that 4% of Salmonella isolates were resistant to gentamicin.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the uncontrolled increase in the usage of prescription antibiotics frequently purchased and used by unqualified practitioners in the veterinary and public health sectors. Also, absence of compliance and monitoring of the antimicrobial drug in developing countries and the utilization of the antimicrobial drugs at sub-therapeutic or prophylactic dosage in food animals may assist in the development and spread of antimicrobial resistance genes in Salmonella as well as other human and animal pathogens (Abdi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…26,27 In Africa, intensification of poultry production has been linked with increased prevalence of Salmonella and decreased prevalence of Campylobacter, but little is known about the association between farm management, biosecurity, and pathogen prevalence in relation to the emerging poultry systems in Tanzania. 8,17 Moreover, it is largely unknown how farmers access information on these topics.…”
Section: Discussionmentioning
confidence: 99%
“…16 The risk of Salmonella contamination can be high in intensive poultry production, particularly if biosecurity is poor. 17 However, intensification does not necessarily increase the prevalence of Salmonella or Campylobacter. For example, both the rise and subsequent fall of Salmonella enterica serovar Enteritidis were associated with intensive poultry production in the United Kingdom (UK), and Campylobacter prevalence was higher in extensively managed indigenous chickens than in intensively managed broilers in the Morogoro Region and Eastern Zone of Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, control of antimicrobial-resistant infections in both humans and animals are of a great challenge because of inadequate adherence to prudent use of antimicrobials, unhygienic living conditions, close con-tact and sharing of houses between animals and humans (Feasey et al, 2012). Different scholars reported antimicrobial resistant Salmonella isolates from categories of food (Weldo et al, 2015;Ejo et al, 2016), animal (Abdi et al, 2017;Kiflu et al, 2017) and human (Eguale et al, 2015;Marami et al, 2018) specimens in Ethiopia. There is an increasing concern with this pathogen due to the emergence and spread of antimicrobial-resistant and potentially more pathogenic strains (WHO, 2012).…”
Section: Introductionmentioning
confidence: 99%